Wie hilfreich ist ein geriatrisches Assessment vor urologischen Operationen im Hinblick auf kognitive Veränderungen? - Wiedemann, A.; Maykan, R.; Pennekamp, J.; Heppner, Hans Jürgen (Aktuelle Urologie, 2015)
Objective: Detection of changes in cognition after transurethral resection (TURP) or 180-Watt green-light XPS laser treatment (GLL) of the prostate is required by the German "Krankenhausbedarfsplan" which demands an interdisciplinary dialogue including special aspects of the operating discipline. This has as yet not been investigated in Germany or in Europe. Methods: Assessments of the cognitive capacity were made by application of the "Mini Mental State Examination" and the "Uhrentest" preoperatively and on postoperative day 2 in addition to documentation of clinical parameters such as patient age, prostate size, duration of surgery, comorbidities, co-medication, changes in haemoglobin and sodium. Results: Patients treated with transurethral resection (n=88) or GLL (n=114) were comparable regarding age, prostate size and operative time. Baseline characteristics of the patients who would be treated with laser showed an increased potential for postoperative cognitive changes: they had an average of 3.8 comorbidities (TURP: 3.11, p=0.005) and were to a greater extent using multiple medications 6.79 (TURP: 5.24, p<0.001). However neither the MMSE nor Uhrentest demonstrated a decrease in the average postoperative score (difference post-preop. MMSE+0.6±1.6 for the GLL and+0.6±1.6 for TURP, p=0.944; difference post- and preoperative Uhrentest+0.43±1.44 for the GLL and 0.13±1.17 for the TURP, p=0.097). Neither the postoperative haemoglobin nor the postoperative sodium, as safety-relevant parameters, demonstrated clinically relevant changes. The differences between the surgical procedures were not statistically significant. 28.6% of the patients with a preoperatively impaired cognition measured by an MMSE-score of≤23.7 incurred a further decline of their cognitive capability in comparison with patients without preoperative cognitive impairment with a further decline in 19.2%. Conclusions: Neither the GLL nor transurethral prostate resection demonstrated changes in cognition by comparing the preoperative Mini Mental State Examination or the Uhrentest. In this study, the baseline characteristics of lasered patients showed a higher number of comorbidities and a higher use of medication, in particular, with anticholinergic potency. Patients with a preoperatively impaired cognition had an increased risk of further worsening of their cognitive capabilities and should be treated carefully.
CRIS-Team Scopus Importer:2022-09-26
Keywords: 180-Watt green light laser; benign prostate syndrome; cognition; operative therapy; prostate hyperplasia; transurethral resection of the prostate; TURP